KESESUAIAN LAHAN TANAMAN JAGUNG DI KABUPATEN MINAHASA SELATAN - Rogi, J. E.X.; Rombang, Johan A.; Kalangi, Josephus I.; Taher, Malsupri (Universitas Sam Ratulangi, 2007)
ABSTRACT Â Rogi, J.E.X. et. al. 2007. The Suistability Land for Corn in the South Minahasa District. Eugenia 13 (3) : 320-326. Based on agri-climate and market prospective, corn is a potential comodity in the South-Minahasa District. From 215.000 ha of South-Minahasa District area, it has 18.437 ha harvest-area and in 2006 produced 52.747 tonnes corn. The above data showed that this district has a possibility to extend the corn planting area in suitable area. To find this suistability area for corn, a spatial data was composed based on soil and climate data using Geographic Information Systemm (GIS). Soil data consisted of texture, pH, C-organic, and cation exchange capacity (CEC), whereas climate data consisted of rainfall and air temperature. Spatial data in the form of land suitability map for corn in the South-Minahasa District was analysed using ArcViewer 3.2. software. Â Keywords: Harvest area, soil and climate, spatial data, GIS, ArcViewer 3.2